Content analysis of regional portals “my documents”: application experience - V. Babakaev, Sergey (2020)
The relevance of topic is due to the search for new approaches and methods used to assess the quality and accessibility of state and municipal services. The aim of the article is to update new approaches to the study of the level of public services on e-government portals and to consider the possibilities of using the content analysis method of “My Documents” regional sites to identify the main directions for improving their work in informing potential service consumers. The leading methodological approach to research is the combination of content analysis methods with expert assessment in the study of sites, based on the integration of the main models for assessing the quality and accessibility of public services. This approach makes it possible to neutralize the weaknesses of existing techniques and to increase their strengths by obtaining a synergistic effect from their application. It opens a new opportunity to consider the work of electronic sites in the context of the regional level of quality standards of information submitted in electronic form, as well as tools and mechanisms of interaction of potential consumers of services with their subject. The main results of the study are generalizations of the experience of using content analysis in the framework of the annual sociological research of the quality of public and municipal services in the Russian regions. The methods are used in assessing the completeness and relevance of the information and information provided, as well as existing opportunities for interaction and feedback with state and municipal authorities and management. The appropriateness and relevance of the study is due to the search for effective mechanisms to ensure standards of quality and accessibility of public services, submitted in electronic form.